More Cooperation, More Benefit?: An Analysis of Modern Trade Agreements - Eszter Kovács (Köz-gazdaság, 2019)
Evolving of free trade agreements creates not just a free, mutually beneficial trade between actors, but may results in elimination of non-tariff barriers. The European Union is by far and away the leader in liberalizing economic and monetary policies, while Canada disposes one of the most open and competitive markets in the world economy, and the United States is the biggest economy in nominal dollars and landing trading country in goods and services. This paper provides four scenarios through a game theoretic model in order to analyze whether players support or except each other in international trade by including the EU, Canada and the USA into the game. Specifically, the article examines that the US withdrawal from TTIP could be explained with the trade integrations impacts on each other.